A survey on social support during standardized training for pediatric residents in Southwest China: a preliminary study - Li, Hongdong; Liu, Jie; Wang, Han; Tan, Liping (Frontiers in Medicine, 2026)
BackgroundThere is little data regarding social support for pediatric residents in standardized training. The aim of this study was to understand the current status and factors influencing social support during standardized training for pediatric residents in Southwest China.MethodsAn electronic survey was administered to pediatric residents from all three professional years at the Children's Hospital of Chongqing Medical University in Chongqing, Southwest China. Pediatric residents anonymously self-provided their demographic information along with social support ratings using the Social Support Rating Scale (SSRS), and multiple logistic regression analysis was performed to evaluate the factors influencing overall social support.ResultsA total of 223 pediatric residents completed the survey and provided valid questionnaires. Overall, 76.23% (170/223) of the participants were satisfied with the level of social support they received. Female pediatric residents demonstrated significantly greater utilization of social support and stronger overall support levels (P < 0.05). Additionally, compared with those who did not have a medical license, pediatric residents who had obtained a physician's medical license reported significantly higher social support levels (P < 0.05). The factors influencing social support were gender, employment and a physician's medical license.ConclusionsThe level of social support for pediatric residents remains suboptimal, with particular attention required for male pediatric residents and those who have not yet obtained their practicing qualifications. It is necessary to formulate and execute better standardized training policies for pediatric residents, increase social support and improve training quality.